CHEMICAL OCULAR INJURY BY POTASSIUM PERMANGANATE: Oral Presentation - Observational Study - General practitioner - Saraya Amajida (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Chemical ocular injury is an emergency case and commonly occured among children. Alkaline chemical ocular injury is more destructive especially due to saponification. One of the rare chemical ocular injury is alkaline trauma by Potassium Permanganate (KMNO4) Methods : A case of a three-year-old boy patient brought by his mother in emergency department at Cicendo Eye Hospital with severe pain, redness, and swelling of the left eye. Ten hours earlier, the patient was playing and accidentally exposed to KMNO4. Visual acuity of the right eye was 6/6 and the left eye was difficult to examine. Ophthalmological examination revealed superior and inferior palpebra are swelling, KMNO4 adhered tightly on conjunctival tarsal superior, inferior, and conjunctival bulbi inferior until fornix and temporal area. Cornea was hazed and iris shadow test positive so he was diagnosed with Chemical Trauma Ropper Hall grade II OS. Treatment begins with irrigation 2 litres of normal saline until pH 7 along with debridement of KMNO4 from conjunctival tarsal superior inferior and bulbi. The patient underwent installation of transplanted amniotic membrane and debridement under anasthesia Results : Management in the initial phase is irrigation. The definitive therapy requires surgery to speed up the healing process. Complications that often occur are corneal limbal cell deficiency, dry eye, symblepharon formation, secondary glaucoma, and complicated cataracts Conclusion : Alkali chemical injury is hazardous and can lead to severe vision threatening complications because of saponification. Prompt and aggressive management is required in such cases to give them the best chance of a more favourable outcome